Stochastic control of individual's health investments - Thomas Glauben; Wilfried Grecksch; Christine Burggraf (Dynamical Systems and Differential Equations, AIMS Proceedings 2015, 10th AIMS International Conference (Madrid, Spain), 2015)
Grossman's health investment model has been one of the most important developments in health economics. However, the model's derived demand function for medical care predicts the demand for medical care to increase if the individual's health status increases. Yet, empirical studies indicate the opposite relationship. Therefore, this study improves the informative value of the health investment model by introducing a reworked Grossman model, which assumes a more realistic Cobb-Douglas health investment function with decreasing returns to scale. Because we introduced uncertainty surrounding individual's health status the resulting dynamic utility maximization problem is tackled by optimal stochastic control theory.
Keywords: 330; stochastic control; Bismut's approach; decreasing returns to scale; health investment model; demand for medical care